Preparation And Characterization Of Superhydrophobic Membrane For Desalination Using Direct Contact Membrane Distillation - Nagarajah, Mohaaneesh (Universiti Sains Malaysia, 2018)
Saline water is the surface water that contains various types of impurities or contaminants. Wastewater also contributes high salinity to the surface water. Therefore, prior treatment of saline water is crucial in sustaining water quality. In this research study, the treatment of saline water is performed by carrying out direct contact membrane distillation (DCMD) which is a thermally driven membrane separation process. A polyvinylidene fluoride (PVDF) superhydrophobic membrane type is casted and modified with the addition of nanoparticles TiO2 and SiO2 in order to increase the membrane surface roughness and hydrophobicity. Silane grafting is also done on the membrane by using hexadecyltrimethoxysilane. The silane grafting was done by varying the silane to ethanol volume ratios of 1:25, 1:50, 1:100 and 1:200. Characterization such as water contact angle, liquid entry pressure (LEP), scanning electron microscopy (SEM), Fourier Transform Infrared Spectroscopy (FTIR) and porosity calculations were done. Based on the water contact angle, modified PVDF-SiO2 membrane with silane ratio 1:50 stated highest average contact angle compared to the other modified membranes which was 141.6°. Therefore, the PVDF-SiO2 (1:50) membrane was used to further perform membrane distillation using distilled water, NaCl solution of 1M concentration and oily NaCl solution. Although the membrane used is modified to almost superhydrophobic condition, however, the fouling phenomenon was still observed by plotting the flux against time curves for each membrane distillation experiments.